1992
DOI: 10.1530/acta.0.1260467
|View full text |Cite
|
Sign up to set email alerts
|

Triiodothyronine (T3) stimulates insulin-like growth factor (IGF)-1 and IGF binding protein (IGFBP)-2 production by rat osteoblasts in vitro

Abstract: Osteoblast-like cells prepared from neonatal rat calvariae and grown under serum-free conditions produce IGF-1 and IGFBPs. In contrast to growth hormone, T3 and PTH increased both IGF-1 mRNA expression and net IGF-1 release in calvaria cells. In addition, they stimulated net production of IGFBP-3 and of an IGFBP with an apparent molecular weight of 32 kDa which was recognized by an antiserum against rat IGFBP-2. Bone cells expressed remarkably high levels of mRNA for IGFBP-2, the predominant IGFBP in serum of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 19 publications
2
31
0
1
Order By: Relevance
“…IGFBP-4 is an inhibitor of cell proliferation, and this may be a mechanism that contributes to the antiproliferative effect of T3 in osteoblasts. T3 also stimulates IGF-I and IGFBP-2 expression in primary rat calvarial osteoblasts, whereas GH has no effect (114).…”
Section: Hormone Action In Skeletal Cellsmentioning
confidence: 97%
“…IGFBP-4 is an inhibitor of cell proliferation, and this may be a mechanism that contributes to the antiproliferative effect of T3 in osteoblasts. T3 also stimulates IGF-I and IGFBP-2 expression in primary rat calvarial osteoblasts, whereas GH has no effect (114).…”
Section: Hormone Action In Skeletal Cellsmentioning
confidence: 97%
“…All these observations support the notion that bone is primarily responsive to T 3 , but that responsiveness is complex and may vary with development and vitamin D or retinoid status. In spite of this, no clearly documented transcriptionally activated T 3 target genes have yet been defined in bone cells, although interleukins-6 and -8 (Siddiqi et al 1996) and IGF binding proteins (IGFBPs)-2 (Schmid et al 1992) and-4 (Glantschnig et al 1996) have been implicated in preliminary studies in human, rat and murine species respectively. Findings of a recent study also suggest that IGF-I may be regulated directly by T 3 in rat vertebral, but not femoral, osteoblasts (Van Auken et al 1997).…”
Section: Thyroid Hormone Actions In Bonementioning
confidence: 99%
“…In humans with hypothyroidism, there are reductions in GH-binding protein, IGF-I, IGF-II, IGFBP-3 and IGF bioactivity; these changes are reversed after thyroid hormone replacement (Miell et al 1993). Furthermore, in studies of cultured rat and mouse osteoblastic cells, it has been suggested that IGFBPs-2 (Schmid et al 1992) and -4…”
Section: Interactions Between T 3 and Igf-imentioning
confidence: 99%
“…IGF-I stimulates bone production by increasing osteoblast proliferation and matrix synthesis (21,22). T3 causes an increase in IGF-I production in UMR-106 osteoblastic cells and bone organ cultures (23,24). IGF-I mRNA in MC3T3-E1 osteoblastic cells is also increased after T3 treatment (25).…”
Section: Discussionmentioning
confidence: 99%